Aplikasi Rizobakteri Pantoea agglomerans untuk Meningkatkan Pertumbuhan dan Hasil Tanaman Jagung (Zea mays, L.) Varietas Hibrida BISI-2 - RAKA, I GUSTI NGURAH; KHALIMI, KHAMDAN; NYANA, I DEWA NYOMAN; SIADI, I KETUT (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012), 2013)
This experiment was conducted in the village of Sibang Gede, District of Abiansemal, Badung Regency on November 2011 until February 2012. The research objective is to enhance the growth and yield of maize hybrid BISI-2 using rhizobacteria Pantoea agglomerans as PGPR in compost formulations. This study used a randomized block design (RBD) single factor with 5 treatments and 5 replications. The treatments tested were P. agglomerans BS7a, P. agglomerans BS7b, P. agglomerans BS2a, and P. agglomerans BS5a. All treatments P. agglomerans formulated in the form of compost and given a dose of 50 g/hole. As a control dose of compost 50 g/hole without PGPR. The results showed that the application of rhizobacteria P. agglomerans increased the maximum plant height, net assimilation rate, crop growth rate, chlorophyll content of leaves, fresh weight of roots per plant, oven dried weight of stover per plant, number of seeds per plant, cob length, cob diameter, seed weight moisture content of 12% per plant and seed yield of 12% water content per hectare.
Keywords: Rhizobacteria, Pantoea agglomerans, corn, growth, and yield